PERAN KETERLIBATAN KERJA, KEPUASAAN KERJA DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI - Yuningsih, Nining (Manageable, 2022)
Organizational commitment is an important role in the progress of a company, this is due to an effort to encourage employees to be more responsible for their obligations. But in reality, there are not a few organizations or companies that pay less attention to commitment. One of the efforts that can be made to increase organizational commitment includes work involvement, job satisfaction and work culture. This study aims to determine how much work involvement, job satisfaction and organizational culture affect organizational commitment in the company. This study uses a quantitative approach with a sample of 85 employees of PT.PAS Cikarang. The method of analysis uses multiple linear analysis using SPSS V.23 software. This study shows that work involvement does not have a significant effect on Organizational Commitment with t count 1.645 < 1.990 while Job Satisfaction does not significantly affect Organizational Commitment with t count 0.367 < 0.1990 and Organizational Culture has a significant effect on Organizational Commitment with t count 8.296 > 1.990 .